2017
DOI: 10.31219/osf.io/hgv3p
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning facts during aging: the benefits of curiosity

Abstract: Background/Study Context: Recent studies have shown that young adults better remember factual information they are curious about. It is not entirely clear, however, whether this effect is retained during aging. Here, we investigated curiosity-driven memory benefits in young and elderly individuals. Methods: In two experiments, young (age range 18-26) and older (age range 65-89) adults read trivia questions, and rated their curiosity to find out the answer. They also attended to task-irrelevant faces presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 1 publication
3
27
1
Order By: Relevance
“…In young and older adults, curiosity states also enhance memory for incidental face images that are encountered during high-compared to low-curiosity states (Galli et al, 2018;Gruber et al, 2014;Stare et al, 2018). In contrast to our prediction, we did not observe that high-curiosity states increased memory for incidental face images in children and adolescents.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In young and older adults, curiosity states also enhance memory for incidental face images that are encountered during high-compared to low-curiosity states (Galli et al, 2018;Gruber et al, 2014;Stare et al, 2018). In contrast to our prediction, we did not observe that high-curiosity states increased memory for incidental face images in children and adolescents.…”
Section: Discussioncontrasting
confidence: 99%
“…To induce curiosity, we used a trivia paradigm in which participants consecutively encoded trivia questions that were associated with varying degrees of curiosity and anticipated the correct answer (see Figure 1). Studies with adults have repeatedly shown that answers to trivia questions associated with high curiosity are better remembered than answers to low-curiosity trivia questions (Fastrich et al, 2018;Galli et al, 2018;Gruber et al, 2014;Kang et al, 2009;Marvin & Shohamy, 2016;McGillivray et al, 2015;Stare, Gruber, Nadel, Ranganath, & Gómez, 2018;Wade & Kidd, 2019). The paradigm consisted of a screening phase in which we selected participant-specific trivia questions for which the answers were unknown and which varied in subjective curiosity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, some of the first neurophysiological curiosity research in humans has approached the topic from the perspective of reward seeking and learning and examined the associated brain regions. When participants study trivia questions and make subjective ratings of their curiosity for the answers, higher curiosity ratings predict greater memory retention (Fastrich, Kerr, Castel, & Murayama, 2017;Galli et al, 2018;Gruber, Gelman, & Ranganath, 2014;Kang et al, 2009;Marvin & Shohamy, 2016;McGillivray, Murayama, & Castel, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Development of curiosity in learning can be used as a component in preparing for the 21st century's superior generation, because it is an important metacognitive skill in the context of education [1]. Individuals who have a high level of curiosity will be able to remember what has been learned longer than individuals who are less curious about the variety of information provided [2] [3]. Besides curiosity plays an important role in maintaining cognitive functions, mental health, and physical [4], and academic achievement [5], so that curiosity is increasingly felt as a virtue that needs to be developed in the learning process in education.…”
Section: Introductionmentioning
confidence: 99%